PERAN BIMBINGAN KARIR DALAM PEMILIHAN JENIS PEKERJAAN SISWA KELAS XII SMK KRISTEN SIMO KABUPATEN BOYOLALI TAHUN PELAJARAN 2015-2016 - Kusumaningtyas, Lydia Ersta (Widya Wacana: Jurnal Ilmiah, 2016)
This study, entitled THE ROLE OF CAREER GUIDANCE IN THE SELECTION OF WORK CLASS XIISMK KRISTEN SIMO BOYOLALI LESSON’S YEAR 2015-2016.The purpose of this study was to determine the role of career guidance in choosing the type of workstudents of class XII SMK Kristen simo Boyolali Year 2015-2016.This is a descriptive qualitative research conducted in SMK Kristen Simo, Boyolali district two monthsfrom November to December 2015. The research subjects are: students of class XII SMK Kristen SimoBoyolali. Data was collected using interview methods (interviews), and observation. To ensure the validityof data used triangulation techniques of observation and perseverance. While the process of data analysisusing data analysis techniques interactive model consists of three components of data analysis, namelydata reduction, data presentation, and conclusion.Based on the results of research and data collection revealed that the application of the guidance mayhelp the student to plan the selection of the type of work on a class XII student of SMK Kristen SimoBoyolali in the academic year 2015/2016. Conducted career guidance counselor can enhance affectiveaspects of students who appear on pleasure, taste is not bored, no trouble and concerned with thedifficulties of students, in addition students are also more independent in choosing a career. So the role ofcareer guidance services in the planning of choosing the type of work the class XII students of SMKKristen Simo Boyolali district is in accordance with what is required of studentsKeywords : CAREER GUIDANCE, THE SELECTION OF WORK